Implementasi MBKM Magang : Tinjauan Pelaksanaan Assembling Rekam Medis Rawat Inap RSU Pekerja PT KGM Jakarta Utara - Leli Mahrani; Robert Edward (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This activity aims to analyze the implementation of inpatient medical record assembly as a document quality control stage at PT KGM Workers' Hospital, North Jakarta. The approach used is descriptive qualitative through direct observation, active participation, and documentation in the Medical Record Unit. The results show that assembling plays a role as an initial quality control that functions to detect incomplete documents before entering the coding and storage stages. Incomplete documents are still found and are related to clinical workload and service time pressure that increase the risk of documentation omission. Adjustments to operational workflows such as the integration of document scanning processes, show system adaptations to improve efficiency and data security. Digitalization supports information traceability, while inter-unit coordination and human resource accuracy are determining factors for documentation quality. It is concluded that inpatient medical record assembly is an important mechanism in maintaining the quality of health information and orderly hospital administration.